Handbook of Federal Indian law - Cohen, Felix S., 1907-1953 (United States Department of the Interior, Office of the Solicitor, 1940)
According to David Selden (Director of the National Indian Law Library and Indian Law research expert), this set provides exhaustive citations to primary law (statutes, cases, secretarial opinions, memos, etc.) impacting each federally acknowledged tribe (up to 1939). It also provides a topical index to primary law (as above) on dozens of Indian law topics (up to 1939).